BIM-Based Construction Information Management Framework for Site Information Management - Dong-Gun Lee; Ji-Young Park; Sang-Hoon Song (Advances in Civil Engineering)
Projects in the construction industry are becoming increasingly large and complex, with construction technologies, methods, and the like developing rapidly. Various different types of information are generated by construction projects. Especially, a construction phase requires the input of many resources and generates a diverse set of information. While a variety of IT techniques are being deployed for information management during the construction phase, measures to create databases of such information and to link these various different types of information together are still insufficient. As such, this study aims to suggest a construction information database system based on BIM technology to enable the comprehensive management of site information generated during the construction phase. This study analyzed the information generated from construction sites and proposed a categorization system for structuring the generated information, along with a database model for storing such structured information. Through such efforts, it was confirmed that such a database system can be used for accumulating and using construction information; it is believed that, in the future, the continual accumulation and management of construction information will allow for corporate-level accumulation of knowledge as opposed to the individual accumulation of know-how.